Developments in Small Molecule Therapeutics Targeted Drug Delivery Systems for the Treatment of Breast Cancer: Present Approaches - Abdulwahed, Abdulhadi M (International Journal of Pharmaceutical Investigation, 2025)
This review aims to discuss the progress made in targeted drug delivery of small molecules in breast cancer, as well as the methods that can be used to increase the accuracy of the treatment and reduce the overall toxicity and resistance. In this work, we described nanoparticle-based drug carriers, antibody-drug conjugates, peptide-drug conjugates, exosome-based delivery and the current role of these systems in increasing the selectivity of the drug delivery to the tumor and drug bioavailability. Furthermore, we reviewed stimulus-controlled drug release systems, RNA-based co-therapies and AI-assisted drug design as the new strategies to enhance the effectiveness of treatment. Finally, we discussed the existing research needs and future trends in hybrid systems, personalized nanomedicine and large-scale production, which can help to understand the prospects of the next generation breast cancer therapies.
Keywords: WHO; TNBC; Chemotherapy; Research gap; MDR; Co-therapy